The Benefits of Smartphone-Based Health Applications in Increasing Knowledge About Preconception Care: A Research and Development Study - Firda Fibrila; Sri Sulistyowati; Muhammad Akhyar; Anik Lestari (Nusantara Science and Technology Proceedings, 2022)
Background: Knowledge influences the use of preconception care. The purpose of developing the application in this study is to obtain health promotion media that can increase knowledge and attitudes about preconception care. Methods: A development study using the Four-D model was carried out in Metro Indonesia from November 2021 to January 2022. Using an experimental design with 60 young women selected in a limited-scale trial. Divided into two groups randomly, where the treatment group has access to utilize information media in the application. Data obtained from pre-test and post-test. Furthermore, the analysis was carried out using the SPSS software version 25.0 using an independent t-test. Result: Application adoption reached 96.67%. The results of the t-test are known, there is a difference of 6.25 in the knowledge variable from the results of the pre-test (41.50) and post-test (47.25), with a t value of 6.542, a significance of 0.001. There is a difference of 1.417 in the attitude variable from the results of the pre-test (36.42) and post-test (37.83), with a value of t = 1.535. Significance of 0.130. Conclusion: There is strong evidence that the media produced has a good performance in increasing knowledge, but has not been able to improve attitudes. For this reason, it needs to be refined to more optimal results.